A cross-national comparison of income gradients in oral health quality of life in four welfare states: application of the Korpi and Palme typology. Issue 7 (6th April 2009) - Sanders, A E; Slade, G D; John, M T; Steele, J G; Suominen-Taipale, A L; Lahti, S; Nuttall, N M; Allen, P Finbarr
Abstract : Background: The extent to which welfare states may influence health outcomes has not been explored. It was hypothesised that policies which target the poor are associated with greater income inequality in oral health quality of life than those that provide earnings-related benefits to all citizens. Methods: Data were from nationally representative surveys in the UK (n = 4064), Finland (n = 5078), Germany (n = 1454) and Australia (n = 2292) conducted from 1998 to 2002. The typology of Korpi and Palme classifies these countries into four different welfare states. In each survey, subjects completed the Oral Health Impact Profile (OHIP-14) questionnaire, which evaluates the adverse consequence of dental conditions on quality of life. For each country, survey estimation commands were used to create linear regression models that estimated the slope of the gradient between four quartiles of income and OHIP-14 severity scores. Parameter estimates for income gradients were contrasted across countries using Wald χ 2 tests specifying a critical p value of 0.008, equivalent to a Bonferroni correction of p<0.05 for the six pairwise tests. Results: Statistically significant income gradients in OHIP-14 severity scores were found in all countries except Germany. A global test confirmed significant cross-national differences in the magnitude of income gradients. In Australia, where a flat rate of benefits targeted the poor, the mean OHIP-14 severity score reduced by 1.7 units (95% CI −2.15 to −1.34) with each increasing quartile of household income, a significantly steeper gradient than in other countries. Conclusion: The coverage and generosity of welfare state benefits appear to influence levels of inequality in population oral health quality of life.